PENGARUH ARUS KAS OPERASI, KONSENTRASI KEPEMILIKAN, DAN BOOK TAX DIFFERENCES TERHADAP PERSISTENSI LABA PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2021 – 2023 - Syuhaibah; Sudiyatmoko, Agus (Publika Citra Media, 2025)
This study aims to determine the effect of Operating Cash Flow, Ownership Concentration, Permanent Differences, and Temporary Differences on Earnings Persistence. The independent variables in this study are Operating Cash Flow, Ownership Concentration, Temporary Differences, and Permanent Differences. The dependent variable in this study is Earnings Persistence. The type of this research is quantitative research. This research uses secondary data in the form of annual financial statements sourced from the Indonesia Stock Exchange (IDX). The population in this study consists of Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange for the years 2021-2023. The sampling technique in this study uses the purposive sampling method, with a total of 14 companies sampled over a period of 3 years, resulting in 42 company samples. Data processing using EViews software version 12 by analyzing descriptive statistics, model fit test, classical assumption test, coefficient of determination, panel data regression analysis, F-statistic test, and T-statistic test. The research results show that (1) Operating Cash Flow, Ownership Concentration, Permanent Differences, and Temporary Differences together significantly affect Earnings Persistence, (2) Operating Cash Flow significantly affects Earnings Persistence, (3) Ownership Concentration significantly affects Earnings Persistence, (4) Permanent Differences do not affect Earnings Persistence, (5) Temporary Differences do not affect Earnings Persistence.